Valor nutritivo e produção de silagem de milho e sorgo inoculados com Azospirillum brasilense - Tonin, Tiago João (2020)
Use of plant growth promoting bacteria (BPCP), especially Azospirillum brasilense, have potential in increase grain and biomass productivity in corn and sorghum plants. This study was conducted with the objective of evaluating the inoculation with A. brasilense in seeds of corn and sorghum hybrids for silage production, regarding the productivity and morphology of the plants at harvest; bromatological quality and digestibility of silages; estimates of energy production, food efficiency and milk production. Corn hybrids AG 8690 and AG 8780 and sorghum hybrids AG 2005 and ADV 2499 were inoculated with strains AbV5 and AbV6 of the A. brasilense bacteria using liquid inoculant AzTotal®. The study was conducted in the 2016/2017 (maize and sorghum) and 2017/2018 (maize) seasons using random block design with treatments composed by inoculated versus non-inoculated hybrids that were evaluated for silage production. For silage, production and dry matter (DM) content, botanical component participation and plant morphology at harvest time were evaluated. In silages, chemical analysis with carbohydrate and protein partition, in vitro digestibility of DM, pH, ammoniacal nitrogen (N) and recovery of MS (DMR) were performed. With the MILK 2006 model, the energy content and milk yield potential of silages were estimated. The efficiency of using N for silage production and milk estimation was also accessed. For silage, no increase in DM production was observed with inoculation in both tested crops, with averages of 16,760 kg DM ha-1 for maize and 13,398 kg DM ha-1 for sorghum. Inoculation increased final plant height, diameter and length in the ears of maize plants, stem diameter and panicle size in sorghum plants. Silages were influenced by inoculation on carbohydrate fractionation, with increased fiber content in acid and neutral detergent in maize and sorghum silages respectively. The starch content in corn silages from inoculated plants was higher, resulting in improved energy content, feed efficiency and estimated milk yield per area. An increase in crude protein (CP) content was observed in the silage of the inoculated AG 2005 sorghum hybrid. In sorghum silage, no improvement in DM digestibility, energy content and estimates of milk production potential was observed with the use of inoculation with A. Brasilense. Inoculation did not increase silage production in corn and sorghum hybrids, but induced morphological changes in the plants. Increased starch and energy content in corn silages and increased CP in sorghum hybrid AG 2005 were the result of inoculation with A. brasilense in the seeds of ensiled hybrids.